"Kultura przemocy" a ludzie starzy = "The culture of violence" and elderly people - Kargul, Józef (1936- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper introduces the academic work performed at the Cultural Animation Unit of the University of Zielona Gora. It focuses on running discussions within the academic seminar. The main part of the article is the example of the problem discussed on the seminar, although infrequently undertaken in the gerontological literature.
Keywords: ludzie starzy; starość; przemoc